3
$\begingroup$

How can I show if the following function is one-to-one? $$y = x^2 - x \ (x \ge \frac{1}{2})$$ A function is one-to-one if $f(x_1) = f(x_2)$ then $x_1 = x_2$. So I put in $x_1$ and $x_2$ in the function and tried to see if $x_1(x_1 - 1) = x_2(x_2 - 1)$ made sense. However, I am stuck right here: how do I know that $x_1 = x_2$ in this situation? I think I might be missing something quite simple...please help!

$\endgroup$
  • 2
    $\begingroup$ $0=f(x_1)-f(x_2)=(x_1-x_2)(x_1+x_2-1)$. Implies that $x_1-x_2=0$, because for $x_1,x_2\geq 1/2$ the factor $x_1+x_2-1\geq0$. $\endgroup$ – user553213 Apr 20 '18 at 10:24
  • $\begingroup$ ... and it is $0$ only when $x_1=x_2=1/2$. $\endgroup$ – user553213 Apr 20 '18 at 10:29
  • $\begingroup$ Clearly you have to use $x_1, x_2\ge 1/2$ since $x^2- x= 0$ for both x= 0 and x= 1. $\endgroup$ – user247327 Apr 20 '18 at 14:38
5
$\begingroup$

From $x_1^2-x_1=x_2^2-x_2$ we get $x_1^2-x_2^2=x_1-x_2$, hence $(x_1-x_2)(x_1+x_2)=x_1-x_2$.

Now assume that $x_1 \ne x_2$. Then it follows that $x_1+x_2=1$. Since $x_1,x_2 \ge 1/2$, we derive $x_1=x_2 =1/2$. Conclusion ?

| cite | improve this answer | |
$\endgroup$
4
$\begingroup$

Hint:

Note that the derivative is $2x-1$ hence is positive for $x>0.5$.

This implies that the function is strictly increasing there.

| cite | improve this answer | |
$\endgroup$
3
$\begingroup$

We can complete the square to write \begin{align*} y & = x^2 - x\\ & = x^2 - x + \frac{1}{4} - \frac{1}{4}\\ & = \left(x - \frac{1}{2}\right)^2 - \frac{1}{4} \end{align*} Can you take it from here?

| cite | improve this answer | |
$\endgroup$
1
$\begingroup$

If $$ x_1^2-x_1=x_2^2-x_2, $$ then you can write $$ x_1^2-x_1-(x_2^2-x_2)=0 $$

What happens if you solve this second degree equation with respect to $x_1$? Since $x_1,x_2\geq \frac{1}{2}$, we may discard the root with negative discriminant and note that the discriminant will be positive. You will have $$ x_1=\dfrac{1+ \sqrt{1-4x_2+4x_2^2}}{2} = \dfrac{1+\sqrt{(-1+2x_2)^2}}{2} = \dfrac{1-1+2x_2}{2}=x_2 $$

Therefore the function is injective.

| cite | improve this answer | |
$\endgroup$
0
$\begingroup$

One strategy is to note that y can be rewritten:

$y =$

$x(x+1)=$

$((x-\frac{1}{2})+\frac{1}{2}))(x-\frac{1}{2})-\frac{1}{2})=$

$(x-\frac{1}{2})^2-\frac{1}{2}$

Since $x>\frac{1}{2}$, $(x-\frac{1}{2})$ is positive, so you're squaring a positive number, which is one-to-one, and subtracting a constant is also one-to-one.

| cite | improve this answer | |
$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.